Maintenance and Safety Requirements of Flameproof and Intrinsically Safe Equipment for Coal Mines - B. Ahirwal; Arvind kumar singh; Rajendra kumar vishwakarm (Institute of Advanced Engineering and Science, 2017)
In the generation of the new technology segment, new explosionproof (Ex) equipment are being installed to make systems suitable for use in hazardous areas of mines. Generally, 80-90% equipment having flameproof (Exd) and intrinsic safety (Exi) methodology of protection are used in the mines for safe operation. The maintenance and safety are two vital parameters to improve the system efficiency of installation in the mines. These parameters are also responsible for the productivity of the mines. The minimum breakdown and maximum safety are the prime concerns of the mines to increase the production. Many observations and basic knowledge are necessary of safety parameters of Ex protections while doing maintenance because micro joules energy is sufficient to ignite the hazardous areas of mines. Trained and skilled personals having good knowledge of Ex protections are required to maintain the limitations of ignition energy sources of Ex equipment to prevent explosion in the mines. A regular and organized scheme of inspection and maintenance may ensure continued, satisfactory and safe operation of Ex electrical equipment in mines. The important points for safety and maintenance of Exd and Exi equipment are pondered in this paper.